Answer:
A ≈ 35.3 units²
Step-by-step explanation:
Calculate the radius CB using Pythagoras' identity in the right triangle.
CB² + AB² = AC²
CB² + 6² = 9²
CB² + 36 = 81 ( subtract 36 from both sides )
CB² = 45 = r²
Then area of quarter circle is
A =
× πr² =
× π × 45 ≈ 35.3
Answer:
19,27 cm^2
Step-by-step explanation:
area of triangle = (6 x 3)/ 2 = 9 cm^2
circle area : 3^2 x 3,14 = 28,27 cm^2
area of shaped region = 28,27 - 9 = 19,27 cm^2
Answer: -8.93
Step-by-step explanation:
Given the function:
N(X) = 90(0.86)^x+ 69
X in the interval [0, 6]
For X = 0
N(0) = 90(0.86)^0 + 69
90 + 69 = 159
For X = 6
N(6) = 90(0.86)^6 + 69
90(0.404567235136) + 69
= 105.41105116224
Therefore, average change of change in temperature ;
(temp 2 - temp 1) / ( time 2 - time)
(105.41105116224 - 159) / (6 - 0)
= - 53.58894883776 / 6
= - 8.93149147296
= - 8.93
Answer:
-1
Step-by-step explanation:
The formula to find the slope of a line is:
![\frac{y_{2}- y_{1} }{x_{2} -x_{1} }](https://tex.z-dn.net/?f=%5Cfrac%7By_%7B2%7D-%20y_%7B1%7D%20%7D%7Bx_%7B2%7D%20-x_%7B1%7D%20%7D)
where (x1, y1) and (x2, y2) are points on the line. We can substitute the points (-10, 0) and (-13, 3) into the formula and simplify:
![\frac{3-0}{-13-(-10)} =\frac{3}{-13+10} =\frac{3}{-3} =-1](https://tex.z-dn.net/?f=%5Cfrac%7B3-0%7D%7B-13-%28-10%29%7D%20%3D%5Cfrac%7B3%7D%7B-13%2B10%7D%20%3D%5Cfrac%7B3%7D%7B-3%7D%20%3D-1)
This means the slope of the line is -1.
6)
34, 43, 52, 61, ...
43-34 = 9; 52-43 = 9; 61-52 = 9
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 34
difference: d = 9
so the formula:
![a_n=a+d(n-1)\\\\a_n=34+9(n-1)\\\\a_n = 34+9n-9\\\\\underline{a_n=9n+25}](https://tex.z-dn.net/?f=a_n%3Da%2Bd%28n-1%29%5C%5C%5C%5Ca_n%3D34%2B9%28n-1%29%5C%5C%5C%5Ca_n%20%3D%2034%2B9n-9%5C%5C%5C%5C%5Cunderline%7Ba_n%3D9n%2B25%7D)
7)
10, 6, 2, -2, ...
6-10 = -4; 2-6 = -4; -2-2 = -4
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 10
difference: d = -4
so the formula:
![a_n=a+d(n-1)\\\\a_n=10+(-4)(n-1)\\\\a_n = 10-4n+4\\\\\underline{a_n=-4n+14}](https://tex.z-dn.net/?f=a_n%3Da%2Bd%28n-1%29%5C%5C%5C%5Ca_n%3D10%2B%28-4%29%28n-1%29%5C%5C%5C%5Ca_n%20%3D%2010-4n%2B4%5C%5C%5C%5C%5Cunderline%7Ba_n%3D-4n%2B14%7D)
8)
-3, -10, -17, -24, ...
-10-(-3) = -7; -17-(-10) = -7; -24-(-17) = -7
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = -3
difference: d = -7
so the formula:
![a_n=a+d(n-1)\\\\a_n=-3+(-7)(n-1)\\\\a_n =-3-4n+7\\\\\underline{a_n=-7n+4}](https://tex.z-dn.net/?f=a_n%3Da%2Bd%28n-1%29%5C%5C%5C%5Ca_n%3D-3%2B%28-7%29%28n-1%29%5C%5C%5C%5Ca_n%20%3D-3-4n%2B7%5C%5C%5C%5C%5Cunderline%7Ba_n%3D-7n%2B4%7D)
9)
7, 8.5, 10, 11.5, ...
8.5-7 = 1.5; 10-8.5 = 1.5; 11.5-10 = 1.5
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 7
difference: d = 1.5
so the formula:
![a_n=a+d(n-1)\\\\a_n=7+1.5(n-1)\\\\a_n =7+1.5n-1.5\\\\\underline{a_n=1.5n+5.5}](https://tex.z-dn.net/?f=a_n%3Da%2Bd%28n-1%29%5C%5C%5C%5Ca_n%3D7%2B1.5%28n-1%29%5C%5C%5C%5Ca_n%20%3D7%2B1.5n-1.5%5C%5C%5C%5C%5Cunderline%7Ba_n%3D1.5n%2B5.5%7D)
10)
30, 22¹/₂, 15, 7¹/₂, ...
22¹/₂-30 = -7¹/₂; 15-22¹/₂ = -7¹/₂; 7¹/₂-15 = -7¹/₂
The difference between one term and the next is a constant so it is arithmetic sequence
first term: a = 30
difference: d = -7¹/₂
so the formula:
![a_n=a+d(n-1)\\\\a_n=30+(-7\frac12)(n-1)\\\\a_n =30-7\frac12n+7\frac12\\\\ \underline{a_n=-7\frac12n+37\frac12}](https://tex.z-dn.net/?f=a_n%3Da%2Bd%28n-1%29%5C%5C%5C%5Ca_n%3D30%2B%28-7%5Cfrac12%29%28n-1%29%5C%5C%5C%5Ca_n%20%3D30-7%5Cfrac12n%2B7%5Cfrac12%5C%5C%5C%5C%20%5Cunderline%7Ba_n%3D-7%5Cfrac12n%2B37%5Cfrac12%7D)